Keterasingan Manusia menurut Karl Marx - Derajat Fitra Marandika (TSAQAFAH, 2018)
Alienation is one of the important concepts of Karl Marx in criticizing capitalism. Marx wanted to create a classless socialist society by the alienation concept. Actually, the concept has captivated various groups, including a number of Muslim thinkers. They use Marxism as a theoretical framework to solve people’s problems today. According to them, Islamic theoretical framework is being irrelevant to solve contemporary problems. In fact, both capitalism and Marx’s socialism were born out of a secular Western paradigm which contradict the principles of Islamic teachings. Muslims must be critical and beware toward the concepts or ideas of Marxism. A Muslim should understand and believe that the best way to solve the problems is not to rely on Marxism, but by understanding and practicing Islamic teachings consistently and comprehensively. Muslims should view the reality integrally with tawhîd framework. It means they should not view the reality secularly or in dichotomy, or deny divine values, or separate two things which are interconnected. The teachings of Marxism regarding alienation refer to the construction of thoughts which are reductionist, atheistic, and contain contradictions that cannot be justified by common sense. Marx’s conception stands on the materialism-dialectics principle. So that, this paper will discuss it further to reveals how the framework of Marxism concerning human alienation. Then, it can be clear description how extent its relevance toward Islamic Worldview.